AI Literacy Framework: the Art and Design Educational Borderline (REVISTA NODO, 2025)
The integration of Artificial Intelligence (AI) into art and design education requires a comprehensive reevaluation of existing curricula and pedagogical approaches, highlighting the need to cultivate AI literacy among managers, educators, and students. The current ambiguity surrounding the definition of AI literacy underscores the need for a structured and revised framework, particularly given the diverse interpretations and implementations in educational settings. This article presents the findings of ongoing research into AI literacy and its importance to art and design education. Through a documentary research method, we reviewed studies that contribute to the discussion of the nature of AI literacy and its implications. Our findings suggest that AI literacy extends beyond technical proficiency, encompassing three abilities: to understand and interpret AI systems, to navigate their ethical implications, and to recognize their broader social and cultural impact within art and design. Recognizing this pivotal moment in AI integration, this article proposes a borderline framework that outlines progressive levels of AI literacy development as it becomes embedded in art and design education. Each level is constructed through the lens of three key dimensions: understanding, ethics, and social impact.
Keywords: Artificial Intelligence; AI; AI Literacy; AI Ethics; Design Education